An analysis of the duplicate testing strategy of an Irish immunochemical faecal occult blood test colorectal cancer screening programme. (18th September 2013) - Kelley, L.; Swan, N.; Hughes, D. J.
Abstract Aim This study examined the relevance of using a two‐sample quantitative immunochemical faecal occult blood test (FIT) at a high cut‐off stringency by the first population‐based colorectal cancer (CRC) pilot screening programme in Ireland. Method Approximately 10 000 individuals between the ages of 50 and 74 years were invited to perform two consecutive FITs. These were analysed in tandem using the OC Sensor and participants with at least one positive result with a haemoglobin cut‐off for positivity at 100 ng/ml were offered colonoscopy. Results A total of 5023 (52%) [2177 (43%) male, 2846 (57%) female] individuals with a median age of 64 years participated. At least one positive FIT was detected from 514 (10%) individuals. From the 419 (82%) patients who proceeded to colonoscopy 17 (4%) had CRC and 132 (33%) had an advanced adenoma. The detection rate for these screen‐relevant lesions was 3% (95% CI 2.5–3.5) and the FIT‐positive colonoscopy detection rate was 36% (95% CI 31–40). The number needed to undergo colonoscopy to find an advanced lesion was 2.8. The two‐test system detected four (23.5%) additional patients with CRC and 37 (28%) with an advanced adenoma compared with a single test. Conclusion The CRC miss rate estimated for a single test (23.5%) was unacceptably high when the goal was to maximize the discovery of advanced lesions in the initial screening round. We conclude that the two‐test protocol at a high cut‐off threshold is suitable for optimizing FIT screening in Ireland.